2017
DOI: 10.3390/children4010006
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Exercise Testing: Value and Implications of Peak Oxygen Uptake

Abstract: Peak oxygen uptake (peakV˙O2) measured by clinical exercise testing is the benchmark for aerobic fitness. Aerobic fitness, estimated from maximal treadmill exercise, is a predictor of mortality in adults. PeakV˙O2 was shown to predict longevity in patients aged 7–35 years with cystic fibrosis over 25 years ago. A surge of exercise studies in young adults with congenital heart disease over the past decade has revealed significant prognostic information. Three years ago, the first clinical trial in children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
13
0
2
Order By: Relevance
“…[3][4][5] Aerobic fitness was measured with a maximal running test on a treadmill with continuous measurement of oxygen uptake (VO 2 peak ). 6 There after a six-minute sub-maximal running test at a speed of 8 km/h and increasing slope of 0, 2.5 and 5% was recorded. After a short rest, running was continued at the same constant speed of 8 km/h while the slope was increased every two minutes by 2.5 or 5%, depending on the heart rate.…”
Section: Methodsmentioning
confidence: 93%
“…[3][4][5] Aerobic fitness was measured with a maximal running test on a treadmill with continuous measurement of oxygen uptake (VO 2 peak ). 6 There after a six-minute sub-maximal running test at a speed of 8 km/h and increasing slope of 0, 2.5 and 5% was recorded. After a short rest, running was continued at the same constant speed of 8 km/h while the slope was increased every two minutes by 2.5 or 5%, depending on the heart rate.…”
Section: Methodsmentioning
confidence: 93%
“…Peak oxygen uptake (VO 2 peak ) is a validated method to measure cardiorespiratory fitness and inactivity generally results in low VO 2 peak . In our previous study, the HENT 1 (HEalth after kidNey Transplantation) performed 2008‐2009, and we showed that children with a renal transplant had a significantly lower VO 2 peak than healthy children .…”
Section: Introductionmentioning
confidence: 89%
“…Neben der subjektiven Einschätzung der körperlichen Belastbarkeit durch Patienten oder deren Eltern gibt es wenige objektive Diagnoseverfahren, um eine umfassende Zustandsbeschreibung von Herz-, Kreislauf-und Atmungssystem eines Patienten, Probanden zu erhalten. Die ergospirometrische Belastungsuntersuchung (englisch: cardio-pulmonary-exercise-test = CPET) ist eines der am besten standardisierten Verfahren für die objektive Einschätzung der Funktion des Respirationstraktes, des Herz-Kreislaufsystems, der neuromuskulären Balance sowie des metabolischen Zustandes in Ruhe und unter Maximalbelastung [7].…”
Section: Hintergrundunclassified